Case Report: Esophageal malignant melanoma with lung adenocarcinoma: a rare case of dual primary cancers - Yang, Li; Yang, Fan (Frontiers in Oncology, 2025)
Primary malignant melanoma of the esophagus (PMME) is a rare type of gastrointestinal melanoma characterized by its aggressive nature and poor prognosis, with a 5-year survival rate of less than 5%. This study reports a case of a male patient with PMME complicated by primary lung adenocarcinoma. The main symptom of the patient was progressive dysphagia. Endoscopically, a polypoid mass was observed protruding into the lumen of the lower esophagus, with melanin pigmentation on the tumor surface, part of which was smooth and part showed ulceration. Enhanced chest and abdominal CT, as well as PET-CT, were consistent with esophageal malignancy, the left lung was consistent with lung cancer, and the right was considered metastatic. CT-guided percutaneous lung biopsy and immunohistochemistry indicated left lung invasive adenocarcinoma. PMME is extremely rare, and the co-occurrence of lung adenocarcinoma as a double primary cancer is even rarer in clinical practice. The disease has a high degree of malignancy and poor prognosis, with diagnosis mainly relying on endoscopic examination, pathological histological morphology, and immunohistochemistry. Early detection and diagnosis are currently key to treating this disease.